2017
DOI: 10.15252/embj.201696003
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative differences in T‐cell activation by dendritic cell‐derived extracellular vesicle subtypes

Abstract: Exosomes, nano-sized secreted extracellular vesicles (EVs), are actively studied for their diagnostic and therapeutic potential. In particular, exosomes secreted by dendritic cells (DCs) have been shown to carry MHC-peptide complexes allowing efficient activation of T lymphocytes, thus displaying potential as promoters of adaptive immune responses. DCs also secrete other types of EVs of different size, subcellular origin and protein composition, whose immune capacities have not been yet compared to those of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
263
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(271 citation statements)
references
References 51 publications
8
263
0
Order By: Relevance
“…As an example of functional heterogeneity consider the release of EVs, rare when the cells are at rest, increased to a large extent, with an at least partially different composition, when the same cells are appropriately stimulated. Similar results, demonstrated in vivo in mice and humans, have also been reported in single cells grown in vitro , when their fluids are significantly changed [2,3,9,10].…”
Section: Extracellular Vesicles: Functions In General Cell Biology Ansupporting
confidence: 85%
“…As an example of functional heterogeneity consider the release of EVs, rare when the cells are at rest, increased to a large extent, with an at least partially different composition, when the same cells are appropriately stimulated. Similar results, demonstrated in vivo in mice and humans, have also been reported in single cells grown in vitro , when their fluids are significantly changed [2,3,9,10].…”
Section: Extracellular Vesicles: Functions In General Cell Biology Ansupporting
confidence: 85%
“…Furthermore, different EV subpopulations isolated from different fractions obtained by ultracentrifugation may have different biological functions. 45 Hence, the concept of EVs as biomarkers in NASH warrants careful validation in clinical studies.…”
Section: Lipotoxic Stress and Extrac Ellular Vesicle (Ev) Releasementioning
confidence: 99%
“…These exosomes, like their parent cells, are able to present allergens and stimulate T-cell responses by direct contact with CD4+ T cells or via the capture of these exosomes by other APCs [31, 32]. In this study, we found that TSLP activated DCs to release exosomes which can induce the production of Th2 cytokines such as IL-4 and promote Th2 differentiation.…”
Section: Discussionmentioning
confidence: 67%